Plan exportador de cerveza artesanal a base de quinua (2022)
In the present project, a series of studies were carried out that will serve for a project to export quinoa craft beer, where a market study was carried out, which led to knowing the production process and the product elaboration process, in the study Market analysis determined that the target market would be the United States, whose foreign trade was analyzed for the process of exporting quinoa beer to its territory. In the same way, important factors for the positioning of the product were analyzed, such as supply, demand and prices.